PERSEPSI MAHASISWA TERHADAP PEMBELAJARAN DARING PERSPEKTIF NEUROSAINS PENDIDIKAN ISLAM - Muhammad Miftakhurrohman; Suyadi Suyadi (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
Online learning is an effort in educational institutions to hold online-based teaching and learning with the intention that the learning process continues according to a predetermined system. This policy is caused by the coronavirus pandemic (COVID-19) which continues to spread and take its toll. This study aims to explain the impact of online lectures on the neuroscience perspective of Islamic education. This study uses qualitative methods, with techniques for collecting data sourced from books, and research journals that are focused on the topic of research. The results showed that the impact of online learning caused students to experience anxiety ranging from not understanding the application and the applied system, to the influence of inner pressure from the coronavirus, which certainly made many students feel stressed. Because of neuroscience the brain has a happy hormone that is the hormone dopamine which response to all conditions that the brain receives. Likewise, the view of Islamic education in denying this is something that is not natural to happen, because it is indirectly detrimental to one party, namely students.